Attachment Styles and the Intensity of Religious Attitude in Secondary School Students - Marchwicki, Piotr (Studia Psychologica: Theoria et praxis, 2003)
The present study investigates in the Polish cultural context some of the results of previously conducted studies on the links between attachment styles and religiousness. Questionnaires containing: a) measures of childhood attachment styles to both parents, level of parental religiousness in childhood and one's own intensity of religious attitude were completed by a sample of 142 secondary school students; b) measures of adult attachment styles and intensity of religious attitude were completed by a sample of 281 secondary school students. The intensity of religious attitude (= IRA) of girls shows no significant relations with either childhood or adult attachment styles. The results obtained for boys support in the main the correspondence hypothesis for links between religiousness and attachment styles in that insecure childhood attachment styles and adult avoidant attachment style correlated negatively with the IRA, and both childhood and adult secure attachment styles correlated positively (even if the cor  lations were not always significant for childhood attachment styles). However, the anxious/ambivalent adult attachment style correlated positively with the IRA which supports the compensation hypothesis for links between religiousness and attachment styles. If parents had had low religiousness the results obtained for both girls and boys indicate a non significant tendency supporting the compensation hypothesis in that substantially secure childhood attachment styles correlated negatively with the IRA, and insecure styles correlated positively.